Student loans repayment and recovery: international comparisons - Hua Shen; Adrian Ziderman (Institute for the Study of Labor (IZA), 2008)
Student loans schemes are in operation in more than seventy countries around the world. Most loans schemes benefit from sizeable built-in government subsidies and, in addition, are subject to repayment default and administrative costs that are not passed on to student borrowers. We probe two issues in this paper, for 44 loans schemes in 39 countries: how much of the original loan is an individual student required to repay (the repayment ratio) and what percentage of the total costs of loans schemes can the lending body expect to receive back in repayments (the recovery ratio)? The analysis shows considerable variation in the size of the repayment and recovery ratios across schemes. Moreover, many loans schemes exhibit sizeable built-in subsidies accruing to student borrowers - in over 40 percent of the schemes examined, the repayment ratio is 40 percent or less. Overall loans recovery is considerably lower. Policy implications of these findings are discussed together with a consideration of steps that may be taken to improve the financial outcome of loans schemes.
urn:nbn:de:101:1-20080711131
Keywords: I22; 330; Student financial aid; student loans; university subsidies; university funding; Studienfinanzierung; Kredittilgung; Hochschulfinanzierung; Subvention; Welt